THE EFFECT OF FOREIGN DEBT, FOREIGN INVESTMENT AND STATE REVENUES ON POVERTY IN INDONESIA - Ichsan Ichsan; Edo Kurniawan (Journal of Malikussaleh Public Economics, 2023)
This study aims to analyze the effect of Foreign Debt (FD), Foreign Direct Investment (FDI) and State Revenue (SR) on the number of poor people in Indonesia. The data used in this study is time series data for 1990-2021 obtained from the Indonesian Central Bureau of Statistics and the World Bank. The data were then analyzed using the Autoregressive Distributed Lag (ARDL) model. The results of this study indicate that, in the short term, the previous 1 year had a negative and significant effect on the number of poor people in Indonesia, while the previous 3 years had a positive and significant effect on the number of poor people. In the long term, foreign debt has a positive and significant effect on the number of poor people in Indonesia. FDI in the previous 0 and 3 year lag had a negative and significant effect on the number of poor people in Indonesia, while 1 year before and 3 years earlier FDI had a positive and significant effect on the number of poor people. In the long term, FDI has a negative and insignificant effect on the number of poor people. SR at lag 0 has a negative and significant effect on the number of poor people in Indonesia, whereas in the previous 3 years SR had a positive and significant effect on the number of poor people. In the long term SR has a negative and significant effect on the number of poor people in Indonesia. Based on the results of this study, it is suggested that the government should carefully calculate the amount of foreign debt needed and pay attention to the distribution of allocations for the use of foreign debt, especially in the poverty alleviation sector. In addition, the government is expected to create a conducive investment climate and increase state revenues, especially through taxes.